Sustaining Outstanding Results (Journal of Universal Excellence, 2026)
Research Question (RQ): How do excellent organizations achieve and maintained outstanding results?Purpose: To determine what criteria and approaches we should use to achieve lasting excellent results in order to maintain excellent results.Method: A qualitative method of reviewing domestic and foreign literature as well as good practices was used for the study.Results: The research confirmed that outstanding results are permanently maintained considering all factors and the people involved according to the EFQM model of excellence.Organization: Leaders develop, define, collaborate, strengthen, and ensure successful management of change in operations of the organizations.Society: Great organizations provide and maintain excellent results that satisfy both the external and the internal stakeholders.Originality: Regardless of the activity they perform, organizations will use the tools and models of business excellence to achieve and maintain their excellence.Limitations/Further Research: The research can be upgraded to other fundamental concepts EFQM model and use it in practice as an implementation of EFQM 2013 model of excellence in the organization. In the following, the research could be extended to the EFQM 2020 model.
Keywords: EFQM excellence model; fundamental concepts of excellence; criteria; enablers; results; stakeholders; integrity